S100A4 accelerates the proliferation and invasion of endometrioid carcinoma and is associated with the “MELF” pattern - Tahara, Shinichiro (Cancer Sci, 2016)
Endometrioid carcinoma (EC) is one of the most common malignancies of the female genital system. Although the behavior of EC ranges from an excellent prognosis to aggressive disease with a poor outcome, the factors that determine its diversity have not been determined. Here, we show that S100A4, a calcium‐binding protein of the EF‐hand type, is correlated with the proliferation and invasion ability of EC. We demonstrated previously that EC cells with high aldehyde dehydrogenase (ALDH) activity were more tumorigenic than ALDH‐lo cells. Screening by shotgun proteomics demonstrated that the expression level of S100A4 in ALDH‐hi EC cells was significantly higher than that in ALDH‐lo cells. S100A4‐knockout cells generated by the CRISPR/Cas9 system showed reduced proliferation and invasion. These cells showed impaired AKT phosphorylation and matrix metalloproteinase‐2 activation, accounting for their impaired proliferation and invasion, respectively. Furthermore, in clinical EC samples, elevated expression of S100A4 was highly related to myometrial and lymphatic invasion in well to moderately differentiated EC. Notably, strong and diffuse expression of S100A4 was observed in tumor tissues with a microcystic, elongated and fragmented (“MELF”) pattern, which is associated with a highly invasive EC phenotype. Collectively, our results demonstrate not only that high expression of S100A4 contributes to an aggressive phenotype of EC, but also that its elevated expression is closely related to the MELF histopathological pattern.